The Sun King at Sea : Maritime Art and Galley Slavery in Louis XIV's France - Martin, Meredith (Meredith S.); Weiss, Gillian Lee
"This richly illustrated volume, the first devoted to maritime art and galley slavery in early modern France, shows how royal propagandists used the image and labor of enslaved Muslims to glorify Louis XIV"--